High metabolic versatility and phenotypic heterogeneity in a marine non-cyanobacterial diazotroph - Crétin, Pauline; Mahoudeau, Louise; Joublin-Delavat, Aurélie; Paulhan, Nicolas; Labrune, Elise; Verdon, Julien; Louvet, Isabelle; Maguer, Jean-François; Delavat, François (Current biology, 2025)
Marine non-cyanobacterial diazotrophs (NCDs) are widespread in the oceans, but the processes controlling nitrogen fixation in cell populations remain understudied. In this study, we combined high-throughput sequencing, genetic and physiological characterization, and single-cell quantification of nitrogenase expression to investigate the growth strategies of the marine NCD Vibrio diazotrophicus. We demonstrate that this marine NCD is highly versatile, capable of utilizing a broad range of organic and inorganic nitrogen sources. Quantitative fluorescence microscopy revealed intense posttranscriptional regulation of nitrogenase expression and that V. diazotrophicus regulates both the proportion of cells and their nitrogenase expression levels based on ammonium concentration in an NtrC-dependent manner. We also found that this phenotypic heterogeneity in nitrogenase expression is more widespread among marine NCDs, suggesting it is a conserved trait. These findings help explain their high abundance in the oceans and deepen our understanding of their ecological importance. [Display omitted] •Intense metabolic rewiring of a marine NCD during diazotrophic growth•High metabolic versatility to explore alternative nitrogen traces in a marine NCD•The proportion of nitrogenase-expressing cells is regulated by NH4+ and NtrC•This phenotypic heterogeneity may be a conserved trait among marine NCDs Crétin et al. unveil the growth strategies of the marine NCD Vibrio diazotrophicus during diazotrophic growth. They demonstrate that cells capture various (in-)organic nitrogen sources and regulate the proportion of nifH-expressing cells in response to NH4+ and NtrC, and that this phenotypic heterogeneity may be a conserved trait among marine NCDs.